Microcontroller based SMS micro e-load vending machine - Cu, Joshua C. (Animo Repository, 2007)
The current period reloading service here in the Philippines involves a retailer inputting both the number and amount specified by the customer, and then the customer checks the number and amount inputted by the retailer. The problem arises when just even one number have been overlooked by both the retailer and the customer which will result to a mismatch, in effect, the customer will not be able to receive the amount of load requested and at the same time the retailer will be forced to reload again which consequently result to profit loss. Considering the amount loaded, their income isn't that much, so in order to address this problem, automating the said service should be of great help to those who are involved in the prepaid reloading industry.;"This thesis project will be composed of a microcontroller, a keypad, an LCD display, a money feeder, a money changer, a GSM module and a power supply. The microcontroller serves as the brain of the whole project this is where all the decisions and calculations happen.Initially, the user inputs the amount using the keypad. Then the user will then be asked for the money to be deposited in the coin acceptor or bill acceptor. Then the device will have to ask for the phone number of the said account. Then the device should prompt a question to proceed or not while displaying the amount and the phone number for visual verification.